ORIENTASI PRODUKTIF: PENGARUH MAKNA KERJA DAN MOTIVASI PADA PEMBENTUKAN KARAKTER TENAGA PENDIDIK - Susminingsih, . (Forum Tarbiyah, 2010)
The understanding of teachers’ position in the educationalprocess departs from the pattern of social interaction and leads tothe pattern of educational interaction. Therefore, the discussion oftheir existence as individuals who interact with their social environmentbecomes absolutely necessary. Human existence consists of severallevels, namely: the first level, anthropological materialism, the secondlevel is biological materialism and the third levels is spiritual beings.Unlike animals, humans have a higher life that is spiritual andintellectual life. Intrinsically this level is independent of everythingthat possesses material character. In the context of work, the natureof human beings as creatures teomorfis in principle, should be definedtheologically, especially in the role of Caliph, correctly and internalizedby every human being through the achievement of the akhlakulkarimah which relies on humanization, emancipation, liberation andtranscendence. In the world of education it is important for theformation of human character who believe, cautious, patient, sincere,affectionate, not easily discouraged oriented and productive